PERSONAL VALUES AND PERCEIVED JOB CHARACTERISTICS AS PREDICTORS OF JOB INVOLVEMENT AND TURNOVER INTENTION AMONG WORKERS IN ANAMBRA STATE, NIGERIA (2014)
Job involvement and employee turnover have been implicated in many studies as serious challenges for organisational management. Although, several factors have been empirically linked with these variables, the role of personal values and perceived job characteristics has not been studied in-depth among workers in Anambra State. This study, therefore, examined the influence of personal values and perceived job characteristics on job involvement and turnover intention among workers in Anambra State. Crossed-sectional survey was adopted, with 504 participants comprising 359 (71.2%) males and 145 (28.8%) females. Among these, 168 (33.3%) participants were randomly selected from each of three sectors; public, organised private and self-employed, using existing records. Personal values as one of the independent variables has ten sub-scales and job characteristics as another, has seven sub-scales. Job involvement and turnover intention as dependent variables have no sub-scale. These variables were measured using personal values scale, job characteristics scale, job involvement scale and turnover intention scale. Data obtained were subjected to ANOVA, multiple comparison statistics and hierarchical regression significant at p<0.05. Public sector workers were less job-involved (F(2,501) = 21.09, p<0.05) and higher on turnover intention (F(2.501) = 255.17, p<0.05) than organised private sector or self-employed workers. Hierarchical regression analysis revealed that personal value factor jointly accounted for 8.0% variance in job involvement among public sector workers, with only the prediction of self-direction slightly significant (β = 0.09, p<0.05). Job characteristics factors increased the variance by 13.0% (R2 = 13, p<0.05), in conjunction with others contributed independently (β = 0.24; p<0.05). On turnover intention, personal values jointly accounted for 10.0% variance but only stimulation predicted independently (β = 0.19; p<0.05). Inclusion of job characteristics resulted in 5.0% change in variance (R2 = 05; p<0.05). In organised private sector, personal values jointly account for 11.0% variance in job involvement with benevolence predicting independently (β = -2.12; p<0.05); variance increased by 4.0% (R2 = 0.04; p<0.05) following inclusion of job characteristics. Personal values jointly accounted for 7.0% variance on turnover intention with only benevolence predicting independently. Inclusion of job characteristics increased the variable by 4.0% (R2 = 0.04; p<0.05) but only autonomy predicted. Among the self-employed, personal values jointly accounted for 8.0% variance in job involvement, while inclusion of job characteristics increased the variance by 4.0% (R2 = 0.04; p<0.05). Workers in Anambra State were influenced by personal values and job characteristics. However, workers in the public sector were the least job-involved and had the highest intention to leave